The The Effect of Implementing Merdeka Curriculum, Learning Facilities, and Teacher Quality on the Learning Achievement of Sekolah Penggerak in East Lombok - Baiq Yang Yuliana Puji Astuti; Muh Fahrurrozi; Farhana Muhammad (Sumber Belajar Sejahtera, 2023)
This study aims to; 1) knowing the effect of the implementation of the merdeka curriculum on student learning achievement in driving schools in East Lombok, 2) knowing the effect of learning fasilities on student learning achievement in driving schools in East Lombok, 3) knowing the effect of teacher quality on student learning achievement in driving schools in East Lombok, especially in driving schools at the Junior High School (JHS) level. This research is a type of quantitative research using a correlational design. The results of this study show; 1) The implementation of an independent curriculum has a partial influence on student learning achievement. 2) Learning facilities have no partial influence on student achievement. 3) Teacher quality has a partial influence on student learning achievement.